Comparison of physical properties of voluntary coughing, huffing and swallowing in healthy subjects - Yawata, Akiko; Tsujimura, Takanori; Takeishi, Ryosuke; Magara, Jin; Yu, Li; Inoue, Makoto (PloS one, 2020)
Coughing, huffing and swallowing protect the airway from aspiration. This study was conducted to compare the physical properties of voluntary coughing, huffing and swallowing in healthy subjects. Ten healthy men were asked to huff, cough and swallow repeatedly. Electromyograms (EMGs) were recorded from the left side of the external oblique (EO), sternocleidomastoid, suprahyoid (SH) and thyrohyoid muscles. Airflow was recorded using a face mask with two-way non-rebreathing valves. The expiratory velocity of huffing and coughing and the SH EMG of all actions presented high intraclass correlation coefficients (> 0.8). The inspiratory and expiratory velocities did not differ significantly between coughing and huffing. The expiratory acceleration of coughing was significantly higher than that of huffing, whereas the expiratory volume of coughing was significantly smaller than that of huffing. The EO EMG of coughing and huffing were significantly larger than that of swallowing. The EO EMG activity during the expiratory phase was significantly higher than that of the other phases of both coughing and huffing. The SH EMG of coughing and huffing were significantly smaller than that of swallowing. Correlation analysis revealed that the expiratory velocity of coughing was strongly positively correlated with that of huffing. The expiratory volume of huffing was significantly positively correlated with hand grip strength. These results suggest that EO and SH muscle activities during huffing or coughing differ those during swallowing, and huffing and coughing may work similarly in expiratory function.